The use of a battery of pain models to detect analgesic properties of compounds: a two‐part four‐way crossover study. (9th January 2017) - Okkerse, Pieter; van Amerongen, Guido; de Kam, Marieke L.; Stevens, Jasper; Butt, Richard P.; Gurrell, Rachel; Dahan, Albert; van Gerven, Joop M.; Hay, Justin L.; Groeneveld, Geert Jan
Abstract : Aim: The aim was to investigate the ability of a battery of pain models to detect analgesic properties of commonly used analgesics in healthy subjects. Methods: The battery consisted of tests eliciting electrical, mechanical and thermal (contact heat and cold pressor)‐pain and included a UVB model, the thermal grill illusion and a paradigm of conditioned pain modulation. Subjects were administered fentanyl 3 μg kg –1, phenytoin 300 mg, (S)‐ketamine 10 mg and placebo (part I), or imipramine 100 mg, pregabalin 300 mg, ibuprofen 600 mg and placebo (part II). Pain measurements were performed at baseline and up to 10 h post‐dose. Endpoints were analysed using a mixed model analysis of variance. Results: Sixteen subjects (8 female) completed each part. The pain tolerance threshold (PTT) for electrical stimulation was increased (all P < 0.05) compared to placebo for (S)‐ketamine (+10.1%), phenytoin (+8.5%) and pregabalin (+10.8%). The PTT for mechanical pain was increased by pregabalin (+14.1%). The cold pressor PTT was increased by fentanyl (+17.1%) and pregabalin (+46.4%). Normal skin heat pain detection threshold was increased by (S)‐ketamine (+3.3%), fentanyl (+2.8%) and pregabalin (+4.1%). UVB treated skin pain detection threshold was increased by fentanyl (+2.6%) and ibuprofen (+4.0%). No differences in conditioned pain modulation were observed. Conclusion: This study shows that these pain models are able to detect changes in pain thresholds after administration of different classes of analgesics in healthy subjects. The analgesic compounds all showed a unique profile in their effects on the pain tasks administered.